Is continuous electronic fetal monitoring useful for all women in labour? - Mullins,E; Lees,C; Brocklehurst,P (BMJ, 2017)
Routine monitoring of all women would prevent much neonatal morbidity, argue Edward Mullins and Christoph Lees, but Peter Brocklehurst believes that it will increase the risk of harm from unnecessary caesarean sections.